Retracing the molecular basis and evolutionary history of the loss of benzaldehyde emission in the genus Capsella. Issue 3 (13th September 2019) - Jantzen, Friederike; Lynch, Joseph H.; Kappel, Christian; Höfflin, Jona; Skaliter, Oded; Wozniak, Natalia; Sicard, Adrien; Sas, Claudia; Adebesin, Funmilayo; Ravid, Jasmin; Vainstein, Alexander; Hilker, Monika; et al.
Summary: The transition from pollinator‐mediated outbreeding to selfing has occurred many times in angiosperms. This is generally accompanied by a reduction in traits attracting pollinators, including reduced emission of floral scent. In Capsella, emission of benzaldehyde as a main component of floral scent has been lost in selfing C. rubella by mutation of cinnamate‐CoA ligase CNL1. However, the biochemical basis and evolutionary history of this loss remain unknown, as does the reason for the absence of benzaldehyde emission in the independently derived selfer Capsella orientalis . We used plant transformation, in vitro enzyme assays, population genetics and quantitative genetics to address these questions. CNL1 has been inactivated twice independently by point mutations in C. rubella, causing a loss of enzymatic activity. Both inactive haplotypes are found within and outside of Greece, the centre of origin of C. rubella, indicating that they arose before its geographical spread. By contrast, the loss of benzaldehyde emission in C. orientalis is not due to an inactivating mutation in CNL1 . CNL1 represents a hotspot for mutations that eliminate benzaldehyde emission, potentially reflecting the limited pleiotropy and large effect of its inactivation. Nevertheless, even closely related species have followed different evolutionary routes in reducing floral scent.